Model of interaction with foreign and national scientific, profit and non-profit organizations, as well as individual scientists within the framework of research infrastructures established in the territory of the Russian Federation - Malyshev, A S; Kolesnikova, E A; Nurakhov, N N; Balyakin, A A; Nurbina, M V; Tsvetus, N Yu; Zaplatina, T S (Journal of physics. Conference series, 2022)
The article considers the issues of methodological and regulatory support for interaction with foreign and national scientific, profit and non-profit organizations, as well as individual scientists in the framework of research infrastructures established in the Russian Federation. The research infrastructures in the neutron field serves as an example, based on which a promising model of international cooperation, aimed at mitigating the negative impact of basic factors that arise when organizing effective interaction with foreign scientific organizations, is considered. The model represents the mechanisms that determine the properties and states of interactions between subjects and describes the processes of forming connections within the framework of the research infrastructure. The article also examines the successful experience of implementing multilateral scientific and technical cooperation within the framework of the activities of existing platforms, associations, forums, etc.